Self-concept, illness acceptance and depressive and anxiety symptoms in people with multiple sclerosis. (July 2021) - Kiropoulos, Litza; Ward, Natalie; Rozenblat, Vanja
Little research has examined the relationship between self-concept and depressive and anxiety symptoms and whether this is moderated by illness acceptance in individuals with multiple sclerosis. Results of an online self-report survey completed by 515 individuals with multiple sclerosis revealed that self-concept was negatively associated with depressive and anxiety symptoms with illness acceptance moderating the association such that individuals with highest self-concept and illness acceptance had the lowest levels of depressive and anxiety symptoms. Findings lend support to psychological interventions that focus on increasing illness acceptance and fostering positive self-concept in individuals with multiple sclerosis.